Orality and literacy in the Demotic tales - Jay, Jacqueline E. (Culture and History of the Ancient Near East, 2016)
In Orality and Literacy in the Demotic Tales , Jacqueline E. Jay extrapolates from the surviving ancient Egyptian written record hints of the oral tradition that must have run alongside it. The monograph's main focus is the intersection of orality and literacy in the extremely rich corpus of Demotic narrative literature surviving from the Greco-Roman Period. The many texts discussed include the tales of the Inaros and Setna Cycles, the Myth of the Sun's Eye , and the Dream of Nectanebo . Jacqueline Jay examines these Demotic tales not only in conjunction with earlier Egyptian literature, but also with the worldwide tradition of orally composed and performed discourse.